2020
DOI: 10.3389/fneur.2020.00272
|View full text |Cite
|
Sign up to set email alerts
|

Altered Resting-State Functional Connectivity of Multiple Networks and Disrupted Correlation With Executive Function in Major Depressive Disorder

Abstract: Background: Major depressive disorder (MDD) is one of the most common and costly psychiatric disorders. In addition to significant changes in mood, MDD patients face an increased risk of developing cognitive dysfunction. It is important to gain an improved understanding of cognitive impairments and find a biomarker for cognitive impairment diagnosis in MDD.Methods: One hundred MDD patients and 100 normal controls (NCs) completed resting-state fMRI (rs-fMRI) scan, in which 34 MDD patients and 34 NCs had scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 64 publications
4
29
0
Order By: Relevance
“…While data analysis approaches of functional brain networks in the context of depression have varied widely, most of them have assessed FC within and between specific networks or regions of interest, of which sensory networks have been considered less of an imperative. On the other hand, when whole-brain analyses are performed, observing abnormalities in the FC involving the visual network are not as rare (Veer et al, 2010;Zeng et al, 2012;Borchardt et al, 2015;Wu et al, 2016;Moreno-Ortega et al, 2019;Schultz et al, 2019;Yan et al, 2019;Liu et al, 2020). These and our results, emphasize the potential implications of this network in the development of the disorder.…”
Section: Strengths and Limitationssupporting
confidence: 68%
“…While data analysis approaches of functional brain networks in the context of depression have varied widely, most of them have assessed FC within and between specific networks or regions of interest, of which sensory networks have been considered less of an imperative. On the other hand, when whole-brain analyses are performed, observing abnormalities in the FC involving the visual network are not as rare (Veer et al, 2010;Zeng et al, 2012;Borchardt et al, 2015;Wu et al, 2016;Moreno-Ortega et al, 2019;Schultz et al, 2019;Yan et al, 2019;Liu et al, 2020). These and our results, emphasize the potential implications of this network in the development of the disorder.…”
Section: Strengths and Limitationssupporting
confidence: 68%
“…In recent years, functional network connectivity (FNC) data obtained from resting-state functional magnetic resonance imaging (rs-fMRI) time series has demonstrated highly informative about the underlying brain connectivity patterns in mental disorders, such as MDD (Mulders et al, 2015 ; Yan et al, 2019 ; Liu et al, 2020 ; Luo et al, 2021 ). Recently, studies have shown that ECT resets and stimulates the formation of the brain regions/networks connectivity (Wang H. et al, 2018 ; Wang J. et al, 2018 ; Bai et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of evidence shows a correlation between the ReHo value of abnormal brain areas and clinical symptoms (Luo et al, 2018). FC usually reflects the connectivity between brain regions to reveal whether there is connectivity disruption or compensation based on independent component analysis and seed point (Liu et al, 2020). All three methods have their own advantages in studying ECN in patients with MCI, but the results are unanimous.…”
Section: Introductionmentioning
confidence: 99%